Pemasukan Elemen 'Ilm Al-Kalam dalam Penghuraian Kaedah Mantik: Analisis Terhadap Percubaan Ilmiah al-Ghazzali - Hamat, Mohd Fauzi (Jurnal Usuluddin, 2002)
There are some approaches that are normally used by Muslim scholars, especially philosophers in explaining and expounding logical laws inherited from the ancient Greeks. A theologian like al-Ghazzali has his own approach which is different from the approaches adopted by other philosophers in some aspects. Al-Ghazzali adopted Islamic approach by introducing and exposing Islamic elements in discussing the law of logic. In his books on logic, al-Ghazzali elaborated some theological issues that would help Muslims to understand the law of logic clearly. Some of his intellectual endeavors are exposed in this article.